KAJIAN LITERATUR TERHADAP GEDUNG PERTUNJUKAN BERDASARKAN STANDAR PERATURAN MENTERI PARIWISATA NO. 17 TAHUN 2015 - Laksana, Azzahra Putri; Kusumaningayu, Intan; Rolalisasi, Andarita (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2024)
Currently, the leading potential of tourism, one of which is based on cultural tourism, needs to improve and develop cultural arts facilities and infrastructure that can accommodate the community, especially art actors to develop freedom in creation. With the existence of various types of art from the creativity of artists can make its own uniqueness for a region.to meet these needs it is necessary to procure, improve, and develop art facilities in an area which can be in the form of outdoor and indoor performance halls to support the creative economy ecosystem and also tourism. In this study, it aims to determine whether the Art Building Facility has been designed based on the Standard Regulation of the Minister of Tourism No. 17 of 2015 concerning Art Performance Building Business.